2016
DOI: 10.1098/rsta.2016.0153
|View full text |Cite
|
Sign up to set email alerts
|

Big data need big theory too

Abstract: The current interest in big data, machine learning and data analytics has generated the widespread impression that such methods are capable of solving most problems without the need for conventional scientific methods of inquiry. Interest in these methods is intensifying, accelerated by the ease with which digitized data can be acquired in virtually all fields of endeavour, from science, healthcare and cybersecurity to economics, social sciences and the humanities. In multiscale modelling, machine learning app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 47 publications
1
150
0
1
Order By: Relevance
“…Big data generating efforts, especially in genomics and the NIH Big Data to Knowledge (BD2K) program, have become an attractive approach for advancing biological discoveries. However, pure big data approaches have been criticized for failing to provide conceptual insights into biological processes (Coveney et al, 2016). It is therefore suggested that big data approaches should rely on theoretical frameworks to avoid circumventing the proven modern scientific method of inquiry and digressing to pre-Baconism methods of radical empiricism (i.e., data generation without reason).…”
Section: Discussionmentioning
confidence: 99%
“…Big data generating efforts, especially in genomics and the NIH Big Data to Knowledge (BD2K) program, have become an attractive approach for advancing biological discoveries. However, pure big data approaches have been criticized for failing to provide conceptual insights into biological processes (Coveney et al, 2016). It is therefore suggested that big data approaches should rely on theoretical frameworks to avoid circumventing the proven modern scientific method of inquiry and digressing to pre-Baconism methods of radical empiricism (i.e., data generation without reason).…”
Section: Discussionmentioning
confidence: 99%
“…This allows the study of alcohol-induced alterations in gene expression in the human brain at an unprecedented level, and the advancement of potentially relevant treatment strategies for normalizing addiction-related changes in gene expression. With these rapid advances also come challenges that are further amplified when considering the broad range of ‘omic’ approaches and modeling requirements for understanding complex disease (Coveney et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…While increasing the availability, scope and amount of interrogable data, this Big Data flood will be of limited use if there is no conceptual framework that grounds the questions to be asked and guides data collection, curation and interpretation, and specifies key variables that need to be measured – and measured accurately . The impact of Big Data on minimising clinical uncertainty may be much more modest than proponents claim.…”
Section: Future Directionsmentioning
confidence: 99%